2009
DOI: 10.1016/j.phymed.2008.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography tandem mass spectrometry identification of proanthocyanidins in rat plasma after oral administration of grape seed extract

Abstract: Proanthocyanidin rich plant extracts derived from grape seed extract (GSE), hawthorn and cranberry are on markets for their preventive effects against cardiovascular diseases and uroinfections in woman. However, the importance of these health beneficial effects of these botanicals remains elusive due to incomplete understanding of uptake, metabolism and bioavailability of proanthocyanidins in vivo. In the present study rats were given GSE orally (300 mg/kg, twice a day) and blood and urine were collected over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 34 publications
(36 reference statements)
2
78
0
1
Order By: Relevance
“…The finding that an oligomer-rich fraction was generally more effective than a monomerrich fraction is intriguing, as the epithelial absorption and systemic bioavailability of PCs is generally regarded to be inversely proportional to size [125][126][127] , consistent with "Lipinski's Rule of 5" for drug bioavailability. This suggests that oligomers, which are largely unabsorbed in their native form, likely act primarily through a mechanism located in the gut.…”
Section: Discussionmentioning
confidence: 87%
“…The finding that an oligomer-rich fraction was generally more effective than a monomerrich fraction is intriguing, as the epithelial absorption and systemic bioavailability of PCs is generally regarded to be inversely proportional to size [125][126][127] , consistent with "Lipinski's Rule of 5" for drug bioavailability. This suggests that oligomers, which are largely unabsorbed in their native form, likely act primarily through a mechanism located in the gut.…”
Section: Discussionmentioning
confidence: 87%
“…Some studies have reported that polyphenols can be found in brain tissue after oral ingestion. For instance, some flavanols, such as metabolites of catechin and epicatechin, can be found in the rat brain following oral intake [9,97,[192][193][194]. Some flavonoids, including dietary anthocyanins such as cyanidin-3-rutinoside and pelargonidin-3-glucoside, are also able to cross the BBB in relevant in vitro and in situ models [195].…”
Section: Brain Bioavailabilitymentioning
confidence: 99%
“…Lower-molecularweight components and metabolites are more easily absorbed (Fernandes et al, 2012;Kosi nska and Andlauer, 2012). Most in vivo studies suggest that procyanidin dimers can be absorbed (Baba et al, 2002;Tsang et al, 2005;Shoji et al, 2006;Prasain et al, 2009). The gut is the predominant location for absorption, a large percentage of the parent compound may be transformed by gut microflora, and the resulting metabolites may constitute the predominant form of absorption (Stoupi et al, 2010).…”
Section: Pharmacokinetics Of Pbesmentioning
confidence: 99%